Diseminasi (Promulgation) atau Penyebarluasan Rancangan Peraturan Daerah Anggaran Pendapatan dan Belanja Daerah (APBD) - Asmar, Abdul Rais (Institut Agama Islam Negeri (IAIN) Bone, 2019)
The draft local regulation (ranperda) compiled at the planning stage needs to be disseminated as a form of openness so as to open the door for community participation, especially strategic regional regulations such as APBD. This paper tries to describe qualitatively through a statutory approach to the problem of spreading the regional budget. Based on a number of samples of the practice of disseminating local regulations and regional regulations in several provices/regencies/cities in Indonesia, there are differences in meditations but are still relatively in accordance with statutory provisions. However, the spread was more when the local regulation was stipulated. As for the planning stage there is no clear picture. This is cause by the indecisiveness of the laws and regulations related to the dissemination of draft regulations, especially strategic regulations such as the regional budget.Rancangan peraturan daerah (ranperda) yang disusun pada tahap perencanaan perlu untuk disebarluaskan sebagai bentuk keterbukaan sehingga membuka pintu partisipasi masyarakat utamanya perda strategis seperti APBD. Tulisan ini mencoba mendeskripsikan secara kualitatif melalui pendekatan perundang-undangan (statutory approach) terhadap permasalahan penyebarluasan ranperda APBD. Berdasarkan beberapa sampel praktik penyebarluasan perda dan ranperda di beberapa daerah provinsi/kabupaten/kota di Indonesia terdapat perbedaan medote tetapi relatif masih sesuai dengan ketentuan perundang-undangan. Akan tetapi, penyebarluasaannya lebih pada saat perda telah ditetapkan. Adapun pada tahap perencanaan tidak terdapat gambaran yang jelas. Hal ini disebabkan oleh ketidaktegasan aturan perundang-undangan terkait penyebarluasan rancangan perda khususnya perda strategis seperti APBD.